Optimal Delegated Search with Adverse Selection and Moral Hazard - Robert Ulbricht (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
The paper studies a model of delegated search. The distribution of search revenues is unknown to the principal and has to be elicited from the agent in order to design the optimal search policy. At the same time, the search process is unobservable, requiring search to be self-enforcing. The two information asymmetries are mutually enforcing each other; if one is relaxed, delegated search is efficient. With both asymmetries prevailing simultaneously, search is almost surely inefficient (it is stopped too early). Second-best remuneration is shown to optimally utilize a menu of simple bonus contracts. In contrast to standard adverse selection problems, indirect nonlinear tariffs are strictly dominated.
urn:nbn:de:bvb:19-epub-20865-2
Keywords: D82; D83; D86; C72; 330; adverse selection; bonus contracts; delegated search; moral hazard; optimal stopping